Comparison of diagnostic accuracy between clinical examination and magnetic resonance imaging (MRI) in diagnosing anterior cruciate ligament (ACL) rupture on Indonesian population - Luthfi Hidayat; Aditya Fuad Robby Triangga; Muhamad Afrizal Farkhan; Bernadeta Fuad Paramita Rahayu; Rahadyan Magetsari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Anterior cruciate ligament (ACL) injury is the most common knee ligament injured. Anterior drawer and Lachman tests are the most common physical examinations for helping diagnose ACL injuries, while magnetic resonance imaging (MRI) is the first choice of supporting examination for evaluating any internal abnormality of the knee. However, studies concerning the accuracy of those examinations in the Indonesian population are limited. This study aimed to compare the accuracy between the anterior drawer test, Lachman test, and MRI in diagnosing ACL injury in Javanese patients. This retrospective study used medical records data of patients who underwent knee arthroscopy in the Department of Orthopaedics and Traumatology, Dr. Sardjito General Hospital, Yogyakarta in 2018. The MRI and the clinical examination results were compared to the arthroscopy results as the gold standard. The study showed the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy for the anterior drawer test were 86.67% (95%CI: 69.28-96.24%), 80% (CI: 44.39-97.48%), 92.86% (CI: 78.88-97.84), 66.67% (CI: 43.28-83.98%), and 85% (CI: 70.16-94.29%), respectively. Lachman test had 96.67% (CI: 82.78-99.92%) sensitivity, 90% (CI: 55.50-99.75%) specificity, 96.67% (CI: 81.86-99.47%) PPV, 90% (CI: 56.44-98.43%) NPV, and 95% (CI: 83.08-99.39%) accuracy. The diagnostic parameters of MRI were 83.33% (CI: 65.28-94.36%) for sensitivity, 60% (CI: 26.24-87.84%) for specificity, 86.21% (CI: 74.21-93.14%) for PPV, 54.55% (CI: 31.77-75.57%) for NPV, and 77.50% (CI: 61.55-89.16%) for accuracy. In conclusion, the Lachman test has better accuracy than the anterior drawer test. Both the anterior drawer and Lachman tests had higher accuracy compared to the MRI.